Nurse or Mechanic? The Role of Parental Socialization and Children's Personality in the Formation of Sex-Typed Occupational Aspirations. - Polavieja, Javier G.; Platt, Lucinda (Social Forces, 2014)
Boys and girls with sex-typical aspirations are significantly more likely to end up in sex-typical jobs as adults. Preference formation among children is therefore relevant for subsequent occupational outcomes. This study investigates the role of parental socialization and children's agency in the formation of sex-typed occupational preferences using data for British children aged 11 to 15. We anchor agency in observable psychological attributes associated with children's capacity to act in the face of constraints. We focus on two such attributes, motivation and self-esteem. Our findings identify two main sources of parental influence: (1) parental sex-typical behaviors, from which children learn which occupations are appropriate for each sex; and (2) parental socio-economic resources, which affect children's occupational ambition. We find, additionally, that girls with high motivation and both girls and boys with high self-esteem are less likely to aspire to sex-typical occupations, net of parental characteristics. Motivation and self-esteem help girls aim higher in the occupational ladder, which automatically reduces their levels of sex-typicality. For boys, however, self-esteem reduces sex-typicality at all levels of the aspired occupational distribution. This suggests that boys with high self-esteem are better equipped to contradict the existing social norms regarding sex-typical behavior. Implications are discussed.